2019
DOI: 10.1177/1758835919877726
|View full text |Cite
|
Sign up to set email alerts
|

First-line systemic therapy for advanced gastric cancer: a systematic review and network meta-analysis

Abstract: Background: Systemic therapy is the standard treatment against advanced gastric cancer. Fluoropyrimidine plus platinum doublet has been recommended as the preferred first-line strategy. However, there is still a lack of a comprehensive and hierarchical evidence that compares all eligible literature simultaneously. Methods: Record retrieval was conducted in PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, ASCO, and ESMO meeting library from inception to October 2018. Randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In China, patients with AGC have poor clinical outcomes and a low 5-year survival rate of <20% ( 53 ). PBC is widely used and plays a crucial role in the treatment of AGC ( 54 ). However, the survival benefit in patients with AGC is still limited; therefore, it is necessary to develop effective combination therapies to increase the efficacy of PBC and reduce side effects in order to prolong the survival time and improve QOL in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In China, patients with AGC have poor clinical outcomes and a low 5-year survival rate of <20% ( 53 ). PBC is widely used and plays a crucial role in the treatment of AGC ( 54 ). However, the survival benefit in patients with AGC is still limited; therefore, it is necessary to develop effective combination therapies to increase the efficacy of PBC and reduce side effects in order to prolong the survival time and improve QOL in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For locally advanced disease, adjuvant or neoadjuvant therapy which recognized as the optimal therapeutic option is usually introduced with surgery owing to its curability 30 . Fluoropyrimidine plus oxaliplatin doublet is considered as the preferred rst-line regimen due to its comparable survival bene ts and lower toxicity 32 . Overcoming resistance is still a challenge in GC chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance has been recognized as one of the difficulties for clinical tumor chemotherapy. DDP is often adopted as a first-line drug for the chemotherapy of gastric cancer patients [12], which can suppress cell vitality and kill tumor cells primarily through inducing apoptosis [13]. However, studies have shown the occurrence of DDP resistance in patients with gastric cancer, which leads to chemotherapy failure and poor prognosis [14].…”
Section: Discussionmentioning
confidence: 99%